Postcard addressed, August 27, 1930, from "O.W." to Brupbacher with quite extensive text on the back. Lenin (left) and Sverlov (in the middle) (1918)
Postcard addressed, August 27, 1930, from "O.W." to Brupbacher with quite extensive text on the back. Lenin (left) and Sverlov (in the middle).